Characteristics of refractory organics in industrial wastewater treated using a Fenton-coagulation process. Issue 22 (2nd October 2021) - Ding, Ran; Zhang, Dandan; Gao, Yingxin; Chen, Xing; Yang, Min
ABSTRACT: It is a challenging environmental issue to develop a cost-efficient approach for the removal of low-concentration refractory organics in industrial wastewater. In this study, the Fenton-coagulation process was utilised to remove the organics from the industrial effluent. The operational conditions of the Fenton-coagulation process were optimised, and then, the molecular weight (MW) and resin fraction distribution of dissolved organic matter (DOM) were investigated before and after the Fenton-coagulation process. The results showed that the efficiency of organic matter removal was affected by the Fe 2+ /H2 O2 molar ratio, pH, and reaction time. The removal rate of chemical oxygen demand (COD) by Fenton-coagulation process reached 37.8% under the following conditions: pH = 4.0 − 5.0, H2 O2 concentration = 34 mg/L, Fe 2+ /H2 O2 molar ratio = 1.5, and reaction time = 120 min. The resin fraction distribution results showed that hydrophobic bases (HoB) were almost completely removed, and the removal rate of hydrophobic acids (HoA) reached 58%, while hydrophilic matter (HiM) became the dominant form in the final effluent after the Fenton-coagulation process due to the appearance of hydrophilic charged fractions (HiC). The results were explained by a two-step mechanism (Fenton oxidation and Fe 3+ coagulation). According to the molecular weight (MW), 35.7% removal of the main fractions of organic matter with MW < 1 kDa was achieved. Furthermore, a pilot test proved that the final effluent quality after the Fenton-coagulation process conformed to the first class of the A discharge standard of pollutants for municipal wastewater treatment plants in Tianjin. GRAPHICAL ABSTRACT: UF0001